Secular trend and spatial analysis of mortality from fibrosis and hepatic cirrhosis in the state of Sergipe in the period from 2001 to 2020 (Research, Society and Development, 2022)
Objective: To analyze the temporal trend and spatial distribution of mortality from fibrosis and liver cirrhosis (LC) in the state of Sergipe from 2001 to 2020. Methodology: Ecological time series study on mortality from fibrosis and LC, from the Information System on Mortality, stratified according to death by year, age group, sex, year of death and municipalities. The standardized mortality rates (SMR) were calculated, using them for trend analysis by the Joinpoint model and in the spatial one by the Kernel density estimator. Results: Over the 20 years, the state of Sergipe had a total of 1.532 deaths from fibrosis and LC. PMS showed an average of 7,12 deaths per 100,000 inhabitants with a predominance of males aged 40-59 years. The time trend of males, aged between 20-39 years (APV=-12,4%) and 40-59 years (APV=-6,1%) showed a reduction in PMS, (p